Test Models for Software Testing - Ab. Ghani, Masnita (2005)
This study is to analyze the test models that are used in there company referred as Company A, B and C. This three company located in Klang Valley and each of them has a different background of business. The objective of this study is to identify the test models that are used by company handling software testing activities steps; features are analyzed from the three test models. A refinement test models are proposed in this study with relevant steps and features.